IMPLEMENTASI KETAATAN DOKUMEN LINGKUNGAN MENURUT UNDANG – UNDANG NOMOR 32 TAHUN 2009 TENTANG PERLINDUNGAN DAN PENGELOLAAN LINGKUNGAN HIDUP OLEH PELAKU USAHA DAN /ATAU PELAKU KEGIATAN DI KABUPATEN BADUNG - Ni Nyoman Indra Deviyani; Lis Julianti (Jurnal Hukum Mahasiswa, 2023)
Implementation of compliance with environmental documents according to the UUPPLH for business actors and/or activities, with supervision efforts from the Badung Regency Environment and Sanitation Service on the level of compliance of those in charge of businesses and/or activities with the provisions of laws. The type of research used in the research used in this research is empirical legal research. In implementing environmental documents, there are still many business actors who have not fulfilled their obligations in accordance with laws and regulations, due to a lack of understanding, commitment, and concern for environmental documents owned by business actors and/or activities to carry out obligations, fulfill requirements, and avoid prohibitions. . The target for the implementation of monitoring of pollution and environmental destruction is set forth in the Budget Execution List (DPA) every year and the realization of its implementation is regulated in accordance with the cash flow which has been determined every month. Business actors and/or activities proven to have violated environmental management are given administrative sanctions in accordance with the violations committed and business actors and/or activities that have complied with environmental management are given appreciation.